Internalization of Pancasila Values through Education in the Era of Globalization: Challenges and Strengthening Strategies - Abyan Faza Shobri; Muhammad Nabil Ahsan (Aslim: Journal of Education and Islamic Studies, 2026)
Pancasila, the fundamental ideology of the Indonesian nation, faces serious challenges in the era of globalization, marked by the open flow of information, technological developments, and the penetration of foreign values. Phenomena such as increasing individualism, the spread of hoaxes, and intolerance in the digital space indicate a degradation of national values ​​rooted in Pancasila. This research aims to emphasize the urgency of strengthening Pancasila values ​​as the nation's ideological bulwark, particularly in building the collective consciousness of the younger generation. Using a descriptive qualitative approach, this study highlights the importance of systematically internalizing Pancasila values ​​through education, digital media, and social role models. The results indicate that revitalizing Pancasila values ​​cannot be done merely formally but must be a continuous and contextual cultural process. This research is expected to make a strategic contribution to strengthening Pancasila's existence as a dynamic and relevant ideology amidst global dynamics.